Epidermis as a Platform for Bacterial Transmission - Baquero, Fernando; Saralegui, Claudia; Marcos-Mencía, Daniel; Ballestero, Luna; Vañó-Galván, Sergio; Moreno-Arrones, Óscar M.; del Campo, Rosa (Frontiers in Immunology, 2021)
The epidermis constitutes a continuous external membrane covering the body, offering protection against bacteria, the most abundant living organisms that come into contact with this barrier. The epidermis is heavily colonized by commensal bacterial organisms that help protect against pathogenic bacteria. The highly regulated and dynamic interaction between the epidermis and commensals involves the host’s production of nutritional factors promoting bacterial growth together to chemical and immunological bacterial inhibitors. Signal trafficking ensures the system’s homeostasis; conditions that favor colonization by pathogens frequently foster commensal growth, thereby increasing the bacterial population size and inducing the skin’s antibacterial response, eliminating the pathogens and re-establishing the normal density of commensals. The microecological conditions of the epidermis favors Gram-positive organisms and are unsuitable for long-term Gram-negative colonization. However, the epidermis acts as the most important host-to-host transmission platform for bacteria, including those that colonize human mucous membranes. Bacteria are frequently shared by relatives, partners, and coworkers. The epidermal bacterial transmission platform of healthcare workers and visitors can contaminate hospitalized patients, eventually contributing to cross-infections. Epidermal transmission occurs mostly via the hands and particularly through fingers. The three-dimensional physical structure of the epidermis, particularly the fingertips, which have frictional ridges, multiplies the possibilities for bacterial adhesion and release. Research into the biology of bacterial transmission via the hands is still in its infancy; however, tribology, the science of interacting surfaces in relative motion, including friction, wear and lubrication, will certainly be an important part of it. Experiments on finger-to-finger transmission of microorganisms have shown significant interindividual differences in the ability to transmit microorganisms, presumably due to genetics, age, sex, and the gland density, which determines the physical, chemical, adhesive, nutritional, and immunological status of the epidermal surface. These studies are needed to optimize interventions and strategies for preventing the hand transmission of microorganisms.